Wadi Shuʿaib, Jordanien. Das Wadi Shuʿaib Archaeological Survey Project – Archäologische Forschungen zwischen Jordantal und transjordanischem Hochland. Die Arbeiten des Jahres 2018 - Ahrens, Alexander (e-Forschungsberichte des DAI, 2019)
The Wadi Shuʿaib Archaeological Survey Project (WSAS) was initiated in 2016. During the fall of 2018, the project’s third survey campaign was conducted in the region of the Wadi Shuʿaib, stretching from the town of as-Salt in the northwest to the Jordan Valley (Shuna South) in the southwest of Central Jordan. In conjunction with the excavations at Tell Bleibil, one main goal of the survey project during the third campaign of the WSAS in 2018 concentrated on a thorough survey of the vicinity of the site of Tell Bleibil (WS-007) in the southern part of the Wadi Shuʿaib, which itself was surveyed in detail during the survey campaigns 2016 and 2017. The survey of the vicinity of Tell Bleibil led to the discovery of four additional archaeological sites, all of which were hitherto unknown. Apart from these newly discovered sites, site WS-010 found by the survey project in 2016, was revisited and found to date to the Epipaleolithic and PPNA periods.